A case report: intravalvular regurgitation during percutaneous valve-in-ring implantation due to eccentric bulging of a balloon-expandable valve in a patient with severe right heart failure. Issue 4 (17th October 2019) - Gerçek, Muhammed; Schramm, René; Paluszkiewicz, Lech; Rudolph, Tanja Katharina
Abstract: Background: Severely reduced right heart function and high operative risk are major challenges in the treatment of tricuspid regurgitation (TR) as both can lead to low cardiac output heart failure (LCO-Hf). Alternative methods and criteria for patient selection are actively being sought. Case summary: We report on a 66-year-old patient with severe right heart failure (rHF) with recurrent TR after prior surgical valve repair with a 32-mm-Edwards-MC3 annuloplasty ring (AR). Surgical revision was discarded due to extreme high surgical risk. A right ventricular assist device was discussed but declined by the patient. Percutaneous edge-to-edge repair was not applicable due to massive tethering of the anterior leaflet and complete lack of coadaptation. According to the Heart team decision, percutaneous tricuspid valve-in-ring implantation was performed using a 29-mm Sapien-3 prosthesis (SP3) under moderate balloon overinflation. Despite satisfying positioning, the prosthesis showed massive intravalvular regurgitation due to immobility of the septally oriented cusp, which was most likely caused by eccentric bulging of the prosthesis in the opening region of the AR. Implantation of a second prosthesis leads to a perfectly functional result. Importantly, no major haemodynamic complications ensued. Discussion: Although being a potential risk of tricuspid valve repair LCO-hf could not be observed in the present case. Additionally, deformation of the implanted transcatheter aortic valve replacement prosthesis resulting from the regional lack of abutment in AR should be considered as a potential complication. Hence, further careful evaluation of the feasibility of percutaneous tricuspid valve treatment, also in patients with rHF, is needed.